The implementation process of designing a digital organization. The problem to determine - Abdulaxatov, Muzaffarjon; Zoirov, Ulmas (Science and Education, 2023)
This paper is based on process of designing a digital organization. And it illustrates how increasing the role of the ICT sector in the modern era.